Impact of Content Marketing, Brand Image, & Social Media on Buying Behavior - Andasari, Alfina; Anshori, Mohamad Yusak (Jurnal Entrepreneur dan Entrepreneurship, 2023)
This research aims to investigate the influence of Content Marketing, Brand Image, and Social Media on purchase intention and purchase decision for Sambal Ning Niniek, a small and medium-sized enterprise (SME). A quantitative research method was employed, with three independent variables, namely content marketing, brand image, and social media, and two dependent variables, namely purchase intention and purchase decision. A total of 216 respondents were included in the study. The analysis involved both outer model and inner model assessments. The results revealed that content marketing did not have a significant positive impact on purchase intention. However, brand image and social media demonstrated a positive and significant impact on purchase intention for sambal Ning Niniek. Furthermore, purchase intention was found to have a positive and significant effect on purchase decisions at Sambal Ning Niniek. Regarding the influence on purchasing decisions, content marketing, and brand image were identified as significant and positive factors for Sambal Ning Niniek. However, social media did not exhibit a significant positive impact on purchasing decisions.